EABR measurements during cochlear implantation in one-year-old, infant, child, adult, and elderly patients. (2nd January 2021) - Enomoto, Chieko; Minami, Shujiro; Kaga, Kimitaka
Abstract: Background: Clinical application of electrically-evoked intracochlear auditory brainstem responses (eABRs) for evaluation of brainstem maturity or aging changes has not been well investigated. Aim/objective: We compare the eV latencies of intraoperative eABR measurements in one-year-olds, infants, children, adults, and the elderly, with the goal of investigating the changes in the brainstem auditory pathway due to development and aging. Materials and methods: We studied 58 ears of 51 patients who underwent cochlear implantation between 2013 and 2019 using MED-EL's Concerto or Synchrony implants with Flex28 or Flex soft electrodes. EABRs were recorded during cochlear implantation. The stimuli were delivered by the MED-EL Maestro to the apical, middle, and basal turn electrodes at stimulus levels 1000, 800, and 600 cu, with a pulse width of 30 µs. Results: In eABRs recorded from electrodes installed at both the mastoid and nape, there was no difference in latency between age groups within each stimulus level. Conclusion and significance: ABR latency was not affected by development after age one and aging of the brainstem auditory pathway. Our study will be useful as a control in identifying abnormal eABR wave configurations in patients with cochlear malformations, cochlear nerve deficiencies, or auditory neuropathy, regardless of age.